International and comparative labour law: current challenges - Bronstein, Arturo (Geneva, 2009)
"Provides an international and comparative account of recent developments in the comparative analysis of labour law, as well as an overview of main current issues. It also advances ideas for a new dynamic balance to accommodate the evolution of labour law and an agenda of possible solutions to current challenges."